Using The Rasch Measurement Model For Standard Setting Of The English Language Placement Test At The Iium - Abu Kassim, Noor Lide (2007)
With the use of cutscores and standards for making high-stakes educational decisions, efforts should be made to search for more defensible standard setting methods.